Utilization of quercetin and quercetin glycosides from onion (Allium cepa L.) solid waste as an antioxidant, urease and xanthine oxidase inhibitors - Nile, Shivraj Hariram; Nile, Arti Shivraj; Keum, Young Soo; Sharma, Kavita (Food chemistry, 2017)
[Display omitted] •Onion solid waste (OSW) used as cheap and valuable source for production of value-added products.•HPLC revealed significant amount of quercetin and quercetin glycosides in OSW.•OSW extracts inhibited the urease and xanthine oxidase activity in vitro.•OSW showed potent antioxidant activity with in vitro scavenging assays. This study aimed to determine the flavonol glycosides from onion solid waste (OSW) using HPLC analysis, with antioxidant and enzyme inhibitory activities. We found considerable amount of quercetin-4′-O-monoglucoside (QMG: 254.85), quercetin-3,4′-O-diglucoside (QDG: 162.34), quercetin (Q: 60.44), and isorhamnetin-3-glucoside (IMG: 23.92) (mg/100g) dry weight (DW) of OSW. For OSW, the methanol and ethanol showed the strongest antioxidant activities, followed by ethyl acetate, chloroform, and n-hexane extracts. Among the flavonols, Q and QDG possessed higher antioxidant activities. OSW and flavonol glycosides displayed significant enzyme inhibitory activity, with IC50 values ranging from 12.5±0.11 to 32.5±0.28 for OSW, 8.2±0.07 to 16.8±0.02 for flavonol glycosides, and 4.2±0.05μg/mL for thiourea (positive control) towards urease; while 15.2±0.8 to 35.8±0.2 (μg/mL) for OSW, 10.5±0.06 to 20.8±0.05 (μg/mL) for flavonol glycosides, and 6.5±0.05μg/mL for allopurinol (positive control) towards xanthine oxidase, respectively. The OSW and flavonol glycosides may thus be considered as potential antioxidant and antigout agents.